Pelatihan Kepemimpinan Pada Mahasiswa LDK AL-HAYYAN Universitas Budi Darma di Medan - Ilhamsyah; Edizal Hatmi; A.M. Hatuaon Sihite (JPM: Jurnal Pengabdian Masyarakat, 2023)
The leadership potential of students who are members of the Campus Da'wah Institute (LDK) organization already exists within them, but in reality the lack of motivation from the surrounding environment causes the leadership spirit of the LDK administrators to not be honed. However, it is not enough from a mental perspective that needs to be addressed. This also requires a strong spiritual soul, so that the mental and spiritual aspects of students can work together. So with the socialization of service activities to Deputy Chairperson III for Student Affairs and LDK chairman Al Hayyan, it can train administrators in improving performance in building this LDK organization so that it is more advanced and has extraordinary motivation. In youth, if you do not have a leadership attitude, you will be displaced and left behind by other people in the organization. Organizations need leadership. The progress and decline of the organization depends on the attitude of its leaders in leading this organization. Thus the inculcation of leadership spirit is very important in order to grow a sense of independence and the emergence of a sense of responsibility for himself, the nation and state organizations